Case study : how Bounteous adopted Agile to provide better service for their clients. (O'Reilly Media, Inc., 2022)
Software development is full of uncertainty. And as a services company, Bounteous has to balance many challenges around that lack of certainty: clients want to be able to make changes, but they still want predictability on time and costs. In the earlier days of its growth, the company struggled with this balance. After considering different methodologies to help address these pain points, Bounteous opted to use Agile because the principles behind it would help the organization embrace a more nimble mindset. But evolving an Agile approach to support this at scale across numerous clients while providing enough flexibility to adapt to specific client situations created several challenges--an experience that really highlights the general problems companies may have in adopting Agile. Join us for this Case Study with Bounteous CTO Seth Dobbs to learn how Bounteous adopted Agile to enable flexibility for its customers while balancing the needs for transparency and predictability across the organization. You'll hear about the roadblocks the company encountered (and how it overcame them) and get insight into how executive support, organizational structure, and team commitment contributed to developing a successful Agile approach. Recorded on February 8, 2022. See the original event page for resources for further learning or watch recordings of other past events. O'Reilly Case Studies explore how organizations have overcome common challenges in business and technology through a series of one-hour interactive events. You'll engage in a live conversation with experts, sharing your questions and challenges while hearing their unique perspectives, insights, and lessons learned. Please note that slides or supplemental materials are not available for download from this recording. Resources are only provided at the time of the live event.